1978
DOI: 10.1007/bf01261238
|View full text |Cite
|
Sign up to set email alerts
|

Pankreasgang-Okklusion durch Injektion einer schnellh�rtenden Aminos�urenl�sung

Abstract: The effect of the occlusion of the pancreatic duct system with a new alcoholic solution of amino acids has been studied in animal experiments. The solution becomes solid in the duct system, is microbiologically indifferent and becomes disintegrated within 11 days. This time, however, is sufficient to keep a high-grade atrophy of the exocrine parenchyma. With this method one doesn't risk the provocation of an acute pancreatitis. The development of fistulas following exploratory excision is prevented by the fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
3

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 17 publications
3
23
0
3
Order By: Relevance
“…Occlusion of the pancreatic duct induces rapid atrophy of the exocrine parenchyma [15]. Accordingly, the median weight of the pancreas in Occ animals is only 3.6% of that in control animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Occlusion of the pancreatic duct induces rapid atrophy of the exocrine parenchyma [15]. Accordingly, the median weight of the pancreas in Occ animals is only 3.6% of that in control animals.…”
Section: Discussionmentioning
confidence: 99%
“…The relative frequency of A-, B-, D-and PP-cells in the pancreatic islets was comparable in both control and Occ pigs. It is concluded that also in the pig pancreatic duct occlusion leads to atrophy of the exocrine pancreas, but leaves undisturbed basal blood glucose, insulin, glucagon and islet cells.Altough there are numerous reports on the general effects of pancreatic duct occlusion in humans and animals [1,10,15,22,24,27], little information is available on the long term influences of this technique on the en 1 Parts of this work have been published in abstract form (Eur. surg.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of the quick-hardening, alcoholic amino acid solution (Ethibloc), are described in experimental studies by Gebhardt and Stolte [3,4]. The injection of this solution into the pancreatic duct leads to necrosis and in the further course to atrophy of the excretory parenchyma and the formation of an interstitial fibrosis, which starts on the 11th day after injection and is completed between the 50th and 60th day with a total extinction of the exocrine part of the parenchyma.…”
Section: Effects Of Prolaminementioning
confidence: 99%